How to deal with sickness absence among primary school pupils? Adaptation of the “Medical Advice for Sick-reported Students” intervention - Pijl, Esther K.; Vanneste, Yvonne T. M.; Mathijssen, Jolanda J. P.; Feron, Frans J. M.; de Rijk, Angelique E. (Frontiers in Public Health, 2023)
Background Missing school impacts both education and health. The purpose of this study was to address sickness absence in primary schools by adjusting the ‘Medical Advice for Sick-reported Students’ intervention for secondary schools. This was necessary because of fundamental differences in relation to the children’s age and in the schools’ organizational structure. Methods The intervention mapping approach steps 1 through 4 were used to adapt ‘Medical Advice for Sick-reported Students’ to primary schools (MASS-PS), including a literature search, stakeholder interviews, establishing a planning group and pre-testing. Results In step 1, a planning group was formed and a logic model of the problem was created. In step 2, a logic model of change was created. In step 3, a theoretical basis and practical strategies were determined. In step 4, practical support materials were designed, and two pre-tests of the materials were performed. Conclusion Intervention mapping was successfully used to adapt MASS to primary schools. The main changes were the lowering of the threshold for extensive sickness absence, consultations between teacher and attendance coordinator, and addition of two experts. With MASS-PS, sickness absence can be addressed as a “red flag” for underlying problems.